Intellectual Capital Disclosure, Kinerja Keuangan Dan Nilai Perusahaan - Adi Reso Sentono; Rina Yuniarti (LPPM Universitas Wijaya Kusuma Surabaya, 2024)
This research aims to examine the effect of intellectual capital disclosure and financial performance on company value in manufacturing companies in 2017–2021. The population in this study consists of 193 manufacturing companies on the IDX during 2017–2021, which were selected based on certain criteria using purposive sampling. The research sample consists of 55 companies with an observation period of 5 years, so there were 275 research sample observations. The type of research conducted in this study was a quantitative descriptive study. The data analysis technique uses panel data regression, which is processed using Eviews. The results of this study indicate that intellectual capital disclosure has a negative and significant effect on company value, while financial performance (ROA) has no effect and is not significant on company value.